Respuesta :
Answer:
[tex]\displaystyle =9x-5[/tex]
Step-by-step explanation:
[tex]\displaystyle 4x-6+5x+1[/tex]
Group like terms.
[tex]\displaystyle 4x-6+5x+1[/tex]
Add the numbers from left to right.
[tex]4+5=9[/tex]
[tex]9x-6+1[/tex]
Add and subtract numbers from left to right to find the answer.
[tex]6-1=5[/tex]
It change to postive to negative sign.
[tex]\displaystyle=9x-5[/tex], which is our answer.
Answer:
The simplified form is 9x - 5
Step-by-step explanation:
It is given an expression in variable x
(4x − 6) + (5x + 1).
To find the simplified form
(4x − 6) + (5x + 1). = 4x − 6 + 5x + 1
= 4x + 5x - 6 + 1
= 9x -5
Therefore simplified form of given expression (4x − 6) + (5x + 1) is,
9x - 5